2020
DOI: 10.3390/plants9081001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ethnobotanical Study of Indigenous Knowledge on Medicinal Plants Used by the Tribal Communities of Gokand Valley, District Buner, Khyber Pakhtunkhwa, Pakistan

Abstract: The current study on the traditional use of medicinal plants was carried out from February 2018 to March 2020, in Gokand Valley, District Buner, Pakistan. The goal was to collect, interpret, and evaluate data on the application of medicinal plants. Along with comprehensive notes on individual plants species, we calculated Use Value (UV), Relative Frequency of Citation (RFC), Use Report (UR), Fidelity Level (FL), Informant Consensus Factor (FCI), as well as Family Importance Value (FIV). During the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 60 publications
(69 reference statements)
4
21
0
2
Order By: Relevance
“…Several studies have confirmed the extensive use of medicinal plants as observed in the present study [42,51,52]. A single plant or parts of a plant species can be used for traditional herbal medicines [22,52]; however, several reports have indicated that a single herbal recipe for particular diseases can be prepared using different plant species [3]. The therapeutic plants are vital in treating diseases of about 80% of the people from emerging economies [53,54].…”
Section: Fidelity Levelsupporting
confidence: 80%
See 3 more Smart Citations
“…Several studies have confirmed the extensive use of medicinal plants as observed in the present study [42,51,52]. A single plant or parts of a plant species can be used for traditional herbal medicines [22,52]; however, several reports have indicated that a single herbal recipe for particular diseases can be prepared using different plant species [3]. The therapeutic plants are vital in treating diseases of about 80% of the people from emerging economies [53,54].…”
Section: Fidelity Levelsupporting
confidence: 80%
“…Moreover, other Asian countries are also investing more energy and money in the discovery of herbal drugs. Asian communities are experts in the usage of medicinal plants for the treatment of common local diseases [3]. Interestingly, both men and women are well informed from their ancestors regarding traditional treatment with medicinal plants.…”
Section: Fidelity Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…The FIV was calculated to identify the significance of plant families and it is an essential index in ethnobotany in estimating the amount of plant taxon. This value was calculated using a formula cited by Sulaiman et al (2020) [22]:…”
Section: Discussionmentioning
confidence: 99%